2015
DOI: 10.1177/0741713615573984
|View full text |Cite
|
Sign up to set email alerts
|

Individual Autonomy or Social Engagement? Adult Learners in Neoliberal Times

Abstract: Numerous scholars have documented and critiqued the predominance of neoliberal policies and rationalities shaping adult and continuing education around the world. Contemporary sociologists have argued that neoliberal citizens are characterized by hyperindividuality and a strong sense of personal autonomy. Self-help reading is widely viewed as one of the most neoliberal forms of adult learning. In this article, we challenge recent claims about the autonomy of the neoliberal subject through reporting results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…We found only minor differences in reading processes and outcomes between relatively younger and older readers , and we documented different patterns of engagement between those whose reading of books relating to mental health was undertaken under the supervision of a therapist and those who read independently (McLean, 2015b). Finally, we found that women reading relationship books rarely internalized explicitly antifeminist messages from those texts , that men were more likely than women to express images of themselves consistent with neo-liberal values such as individual autonomy (McLean, 2015a), and that men presented narratives about themselves as readers that were overwhelmingly consistent with the tenets of hegemonic masculinity (McLean & Vermeylen, 2017).…”
Section: Resultsmentioning
confidence: 63%
“…We found only minor differences in reading processes and outcomes between relatively younger and older readers , and we documented different patterns of engagement between those whose reading of books relating to mental health was undertaken under the supervision of a therapist and those who read independently (McLean, 2015b). Finally, we found that women reading relationship books rarely internalized explicitly antifeminist messages from those texts , that men were more likely than women to express images of themselves consistent with neo-liberal values such as individual autonomy (McLean, 2015a), and that men presented narratives about themselves as readers that were overwhelmingly consistent with the tenets of hegemonic masculinity (McLean & Vermeylen, 2017).…”
Section: Resultsmentioning
confidence: 63%
“…In countries with a democratic tradition in adult learning such as Sweden, institutions like folk high schools provide space for collective learning about democracy and they serve to temper individualisation tendencies that would attempt to remould learners as neoliberal subjects [11]. Under the neoliberal discourse is an assumption about a hyper-individualised learner but this dichotomy between individual autonomy and social engagement has been found to be more complex than thought where even the purest form of self-help learning undertaken by individuals alone would contain elements of social engagement in it [12]. Thus said, it would not yet be a vain effort to pursue group-based learning under a climate of neo-liberal influenced learning which has dominated the centre-stage of ALE worldwide.…”
Section: Theoretical Perspectives On Ale Practicementioning
confidence: 99%
“…Distintos trabajos emplean el término de caracterización o caracterización del yo. En la mayoría de los casos, se describen perfiles psicopatológicos (Müller, Beutel y Wölfling, 2014) o perfiles de personalidad (Farkas y Orosz, 2013); en otros casos, se describen categorías de contenido temático (Lindquist y Barrett, 2008) y también se plantean como descripciones narrativas que sirven para obtener información del yo sin un esquema prefijado (McLean, 2015;Traen y Sorensen, 2008;Stephenson, Laszlo, Ehmann, Robert M. H. Lefever y Robin Lefever, 1997). George A.…”
Section: Introductionunclassified